Association between tumor-infiltrating lymphocytes and oncotype DX estrogen receptor, progesterone receptor, and human epidermal growth factor receptor 2 single gene scores in hormone receptor-positive/HER2-negative breast cancer - Ohara, Masahiro; Mikami, Emi; Inohana, Wakako; Kurosawa, Taeko; Nakame, Ayako; Sakakibara, Ayaka; Ichinose, Yuki; Fujimoto, Akihiro; Nukui, Asami; Asano, Aya; Shimada, Hiroko; Asai, Kyoko; et al. (Frontiers in Oncology, 2026)
IntroductionTumor-infiltrating lymphocytes (TILs) are established biomarkers in triple-negative and human epidermal growth factor receptor 2 (HER2)-positive breast cancers; however, their clinical significance in hormone receptor-positive, HER2-negative (HR+/HER2−) breast cancer remains unclear. This study aimed to investigate the association between TILs and Oncotype DX single gene scores for estrogen receptor (ER), progesterone receptor (PgR), and HER2 in HR+/HER2− breast cancer.MethodsWe retrospectively analyzed 260 patients with HR+/HER2− breast cancer who underwent surgery and Oncotype DX testing at Saitama Medical University International Medical Center between January 2022 and October 2024. TILs were evaluated on hematoxylin and eosin–stained slides according to the International TILs Working Group 2014 guidelines, with high TILs defined as ≥10%. Associations between TILs, clinicopathological factors, and Oncotype DX single gene scores were examined using statistical analyses, including logistic regression. Additionally, publicly available data from The Cancer Genome Atlas (TCGA) cohort were analyzed for validation.ResultsHigh TIL levels were observed in 32 cases (12.3%). Tumors with high TILs showed significantly lower Oncotype DX single gene expression of ER (9.8 ± 1.9 vs. 10.5 ± 1.3, p < 0.01), PgR (6.3 ± 2.2 vs. 7.4 ± 1.8, p < 0.01), and HER2 (8.5 ± 0.7 vs. 9.2 ± 0.6, p < 0.001) compared with tumors with low TILs. Multivariate analysis identified node-negative status (odds ratio [OR]: 0.266; p = 0.0159) and lower HER2 single gene expression (OR: 0.293; p = 0.00144) as independent predictors of high TILs. TCGA analysis confirmed that lower HER2 mRNA expression was associated with increased chemokine gene expression.DiscussionIn HR+/HER2− breast cancer, tumors with lower HER2 mRNA expression exhibit higher lymphocytic infiltration, suggesting the presence of a distinct immunologically active subset. Oncotype DX single gene scores, particularly HER2, may provide information beyond recurrence risk prediction and help identify patients who may benefit from immune-modulating therapeutic strategies.